2007
DOI: 10.1192/bjp.191.51.s88
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of treatment for prodromal symptoms for people putatively in a late initial prodromal state of psychosis

Abstract: Coadministration of amisulpride yielded a marked symptomatic benefit. Effects require confirmation by a placebo-controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 31 publications
1
99
0
9
Order By: Relevance
“…Extrapyramidal symptoms did not differ between groups. Ruhrmann et al (2007) used a somewhat different approach in their study comparing a supportive needs-focused intervention with and without amisulpride in 124 individuals with putative prodromal symptoms. Rather than evaluating conversion rates, their main outcome criterion was the improvement in various prodromal symptoms including Attenuated Positive Symptoms (APS), Brief Limited Intermittent Psychotic Symptoms (BLIPS), and Basic Symptoms (BS).…”
Section: Pharmacological Interventionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Extrapyramidal symptoms did not differ between groups. Ruhrmann et al (2007) used a somewhat different approach in their study comparing a supportive needs-focused intervention with and without amisulpride in 124 individuals with putative prodromal symptoms. Rather than evaluating conversion rates, their main outcome criterion was the improvement in various prodromal symptoms including Attenuated Positive Symptoms (APS), Brief Limited Intermittent Psychotic Symptoms (BLIPS), and Basic Symptoms (BS).…”
Section: Pharmacological Interventionsmentioning
confidence: 98%
“…The main side effect of amisulpride was a non-dose-dependent increase in prolactin levels. Ruhrmann et al (2007) make the point that patients with prodromal signs or symptoms should not only be managed to reduce the risk of conversion to psychosis but also to treat their subjective suffering.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that young people in particular are prone to neuroleptic side effects (Fraguas et al, 2008) whilst long term use carries the possible risk of brain shrinkage (Ziermans et al, 2011). Indeed significant side effects have been noted in several At-Risk Mental State trials thus far, such as weight gain (McGlashan et al, 2006, and increased prolactin levels resulting in high study drop out (Ruhrmann et al, 2007). Although it is relatively easy to highlight the sideeffects and potential negatives of medication use, limited attention has been directed towards the use of psychological therapies that have also been utilised as a form of psychosis prevention.…”
Section: The Risks Of Being Labelled 'At-risk'mentioning
confidence: 99%
“…The main outcome variable was prevention of conversion into manifest schizophrenia. Four RCTs in people with prodromal symptoms assessing the efficacy of new-generation antipsychotics (NGAs) suggest that the use of NGAs (amisulpride, olanzapine, and risperidone) in UHR individuals may delay the onset of frank psychosis, ameliorate subthreshold psychotic symptoms, and improve functioning [12][13][14][15], although three of the trials failed to demonstrate statistical significance on the main outcome variable. These trials involved a relatively small number of subjects.…”
Section: Early Intervention At the Prodromal Stagementioning
confidence: 99%